Hubungan antara Kepercayaan Diri dengan Prestasi Belajar dan Perencanaan Karir Siswa SMP - Indra Bangkit Komara (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2016)
This research aimed to know the relationship between self confidence with students’ achievement and career planning of grade VIII SMP Negeri 3 Bantul. The research used quantitative approach with correlation type. Research subjects were 93 students who were taken through random sampling technique from 186 populations of students. Data analysis technique which was used to know correlation between variables was double linear correlation. The analysis result showed determinate coefficient value (R²) =0.528, it means that the high expectation for career planning was caused by self confidence and students’ achievement was 52.8% and the rest 47.2% was caused by other variables such as physics, psychology, and environment.  It can be concluded that there re is a positive correlation between self confidence and students’ achievement with students’ career planning of grade VIII SMP Negeri 3 Bantul. The research results are beneficial for counselors as the description of self confidence, students’ achievement, and career planning condition which can be considered in arranging guidance and counseling services program for students at school.